2021
DOI: 10.5194/acp-2021-282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zeppelin-led study on the onset of new particle formation in the planetary boundary layer

Abstract: Abstract. We compared observations of aerosol particle formation and growth in different parts of the planetary boundary layer at two different environments that have frequent new particle formation (NPF) events. In summer 2012 we had a campaign in Po Valley, Italy (urban background) and in spring 2013 a similar campaign took place in Hyytiälä, Finland (rural background). Our study consists of airborne and ground-based measurements of ion and particle size distribution from ~1 nm. The airborne measurements wer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Field measurement data are available in ebas.nilu.no and https://actris.nilu.no/. The Zeppelin-relevant, San Pietro Capofume and Bologna data are available in https://doi.org/10.5281/zenodo.4660145 (Lampilahti et al 2021). The field datasets for Patras, Thessaloniki and Costa Navarino can be obtained after request to the authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field measurement data are available in ebas.nilu.no and https://actris.nilu.no/. The Zeppelin-relevant, San Pietro Capofume and Bologna data are available in https://doi.org/10.5281/zenodo.4660145 (Lampilahti et al 2021). The field datasets for Patras, Thessaloniki and Costa Navarino can be obtained after request to the authors.…”
Section: Discussionmentioning
confidence: 99%
“…A SMPS was used to measure the number size distribution of particles in the size range of 10 to 430 nm. Details of the relevant PEGASOS Zeppelin measurements can be found in Lampilahti et al (2021).…”
Section: Model Application and Measurementsmentioning
confidence: 99%
“…Since Nilsson et al. (2001), studies have utilized airborne measurement platforms and found NPF occurring at various levels within the mixed layer and often near the top of the mixed layer (e.g., Boulon et al., 2011; Chen et al., 2018; Lampilahti, Leino, et al., 2021; Lampilahti, Manninen, et al., 2021; Leino et al., 2019; Nikandrova et al., 2018; Platis et al., 2016; Qi et al., 2019; Schobesberger et al., 2013; Wehner et al., 2007, 2010). These enhancements are still thought to be a result of the mechanisms (a–d) from Nilsson et al.…”
Section: Introductionmentioning
confidence: 99%
“…A Zeppelin is an ideal airborne platform to capture the vertical distribution of pollutant concentrations and gain insights into their origin and emission sources (Lampilahti et al, 2021;Li et al, 2014;Nieminen et al, 2015). It offers enough room to deploy equipment and flies precisely and slowly at desired heights.…”
Section: Introductionmentioning
confidence: 99%